Spatio-temporal analysis of water quality for pesticides and other agricultural pollutants in Deduru Oya river basin of Sri Lanka - Jayasiri, M.M.J.G.C.N.; Yadav, Sudhir; Dayawansa, N.D.K.; Propper, Catherine R.; Kumar, Virender; Singleton, Grant R. (Elsevier, 2022)
The desire to increase agricultural productivity through the high usage of agrochemicals is causing substantial environmental deterioration. Many developing countries lack the capacity to quantify agro-pollution, especially in the case of chemical inputs such as pesticides, preventing them from formulating action plans to mitigate the negative environmental impacts of agro-chemicals. This study aims to address the knowledge gap in Sri Lanka by assessing water quality at a temporal and geospatial scale, focusing on areas with significant agricultural inputs in the Deduru Oya river basin of Sri Lanka. To assess water quality, 183 samples were collected biweekly in the 2019 dry season (Yala) and 2019/2020 wet season (Maha) and analyzed for 39 parameters, including pesticides, heavy metals, minerals and physico-chemical properties. Of the twenty pesticides tested, ten were detected in the water samples (pretilachlor, oxyfluorfen, thiamethoxam, chlorantraniliprole, fenobucarb, fipronil, diazinon, etofenprox, tebuconazole, and captan) and concentrations of all detected pesticides exceeded national regulatory threshold limits. Heavy metal residues were not detected in the water. Pesticide and mineral levels varied widely and exhibited lack of evenness across seasons and locations. Pesticide contamination was higher in the wet season than the dry season. Temporal variation was more pronounced than spatial variation for many of contaminants. No clear trend in contaminant accumulation was observed as sampling progressed downstream from the main reservoir. In both seasons, natural or inorganic fertilizer mineralization and pesticide inputs into the agricultural systems were identified as the main factors underlying water pollution in the study area.